Economic impact and conservation potential of shark-diving tourism in the Azores Islands - Gonzáles-Mantilla, Pedro G.; Gallagher, Austin J.; León, Carmelo J.; Vianna, Gabriel M. S. (Marine Policy, 2022)
Shark-diving tourism is an emerging industry in the Azores Islands. However, this industry directly competes with fishing, as both exploiting the same highly migratory shark species. This study quantifies the commercial value of the Azorean shark-diving industry based on a survey of dive tourists and local dive operators and the potential of this industry to further generate funds for implementation of direct conservation actions. The economic contribution of the shark-diving industry to the regional economy of the Azores in 2019 was estimated to be just over USD $ 1 Million. The results of a spiked censored interval data model of contingent valuation indicated that implementation of an extra conservation fee per dive trip, to be paid by dive tourists, could potentially yield over USD $ 103,000 per year to be used for management and enforcement of a proposed MPA for sharks around the dive sites. Our analysis suggests that the emerging shark-diving industry in the Azores Islands has potential to grow throughout the Macaronesian archipelago, thereby increasing tax revenues and the number of jobs and income to Azorean local communities, potentially promoting conservation and sustainable use of the shark populations. However, expansion of this industry into a robust contributor to the archipelago's economy would require a concomitant strengthening of industry regulation, and support by the government, to protect businesses and investments. This could be partially obtained through improving in fisheries management, implementation of a functional MPA and adequate enforcement. 1,355 4,173 Q1 Q1 SSCI 11,0